K-POP FAN BEHAVIOR AMONG ISLAMIC ECONOMICS STUDENTS: A MAQĀṢID SHARĪʿAH PERSPECTIVE - Marlina Marlina; Muh. Arafah; Hartas Hasbi (Universitas Islam Darul 'ulum Lamongan, 2025)
Research on K-pop fan behavior among Islamic Economics students, particularly from the perspective of maqāṣid sharīʿah, remains scarce. This study aims to fill this gap by analyzing the balance between K-pop fandom and the academic, economic, and religious responsibilities of female students at the Islamic Economics Program of IAIN Bone. This research employs a qualitative field research methodology with an Islamic Economics approach, focusing on consumption behavior. The study investigates the specific behaviors of K-pop fans within the 2021 cohort of these students and analyzes how these behaviors align with maqāṣid sharīʿah. Data was primarily collected through interviews with students actively engaging with K-pop culture and managing related expenses. Findings indicate that students tend to be selective and rational in consuming K-pop products, considering economic factors like limited income, prices, and other needs. Socially and culturally, K-pop fandom serves not only as entertainment but also motivates skill development, such as learning Korean and understanding global culture. From the maqāṣid sharīʿah perspective, the behavior is analyzed through Ḥifẓ al-dīn (preservation of religion), where students maintain worship and avoid excessive fanaticism; Ḥifẓ an-nafs (preservation of self/soul), where fandom positively impacts mental well-being and motivation; and Ḥifẓ al-māl (preservation of wealth), where students demonstrate financial prudence, distinguishing needs from wants and avoiding excessive consumption.